2012
DOI: 10.1118/1.4711757
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided identification of cardiac imaging windows

Abstract: In this study, the authors showed that IVS velocity can be used to identify periods of diastasis for coronary arteries. Despite variability in mid-diastolic rest positions over multiple steady rate heartbeats, vessel blurring of 0.5-1 mm was found to be achievable using the IVS gating technique. The authors envision this leading to a new cardiac gating system that, compared with conventional ECG gating, provides better resolution and shorter scan times for coronary MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Different epicardial regions have been known to have different diastasis timings [4,5,16]. The Septal Scout is more suitable for whole-heart angiography; basal septal diastasis is an accurate surrogate for ventricular diastasis [9]. To our knowledge, there has not been work presented on the CMR monitoring of septal motion for determining cardiac gating windows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different epicardial regions have been known to have different diastasis timings [4,5,16]. The Septal Scout is more suitable for whole-heart angiography; basal septal diastasis is an accurate surrogate for ventricular diastasis [9]. To our knowledge, there has not been work presented on the CMR monitoring of septal motion for determining cardiac gating windows.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it observes the expansion and compression of the basal interventricular septum (IVS) along the long axis of the heart, which has been found to correlate with global epicardial motion [9]. The high temporal resolution is achieved by foregoing one dimension of spatial encoding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al showed that the IVS was an accurate predictor of LAD vessel quiescence. 16 From Table III, the LAD is in fact among the least similar to the IVS, suggesting that if the IVS is a suitable predictor for the LAD it will be as good or better for the other vessels. The quiescence of the IVS is of particular interest because it can be readily observed using echocardiography, as opposed to the coronary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate timing determination for whole-heart coronary imaging can be difficult in such subjects, as the heart rate can vary from beat to beat over the duration of a long scan, or change significantly in the presence or absence of breath-holding. In addition to the per-patient and physiological variability, the optimal period quiescent period with minimal motion for each artery branch may vary by anatomical position [10,11]. Therefore, a single acquisition window may not necessarily be optimally timed for each coronary artery branch and region.…”
Section: Introductionmentioning
confidence: 99%